Elucidating the Consumer Perception for Coir Composite Furniture: A Move towards Sustainable Consumption - Gayathri RAMESH; A.S. Ambily (Communications of International Proceedings, 2020)
The present research aims to understand the perception of respondents pertaining to furniture made of Coir Composite Board. The study made an attempt to measure the strength of various attributes in order to get a better insight with regard to CCB as an environment friendly furniture stock. A survey was conducted through structured questionnaire for people who visited the International Coir Fest in Kerala, India 2019. Of the attributes chosen, the results highlighted the greatest strength of CCB furniture being ‘environment friendly’, ‘good finish’ and ‘surface smoothness’. The research could aid the management and manufacturers to target their customers with proclivity towards Environmental-Economical-Societal Sustainability. With advent in its competitive price, the market potential of furniture made of CCB is to bring a major change in the panel board industry, the construction industry in totality. ,
Keywords: Coir Composite Board; perception; environment sustainability.